Electric Pulses Can Influence Galvanotaxis of Dictyostelium discoideum. (8th August 2018) - Li, Ying; Gu, Yu; Wang, He; Liu, Zhipeng; Song, Bing; Yin, Tao
Abstract : Galvanotaxis, or electrotaxis, plays an essential role in wound healing, embryogenesis, and nerve regeneration. Up until now great efforts have been made to identify the underlying mechanism related to galvanotaxis in various cells under direct current electric field (DCEF) in laboratory studies. However, abundant clinical research shows that non-DCEFs including monopolar or bipolar electric field may also contribute to wound healing and regeneration, although the mechanism remains elusive. Here, we designed a novel electric stimulator and applied DCEF, pulsed DCEF (pDCEF), and bipolar pulse electric field (bpEF) to the cells of Dictyostelium discoideum . The cells had better directional performance under asymmetric 90% duty cycle pDCEF and 80% duty cycle bpEF compared to DCEF, with 10 Hz frequency electric fields eliciting a better cell response than 5 Hz. Interestingly, electrically neutral 50% duty cycle bpEF triggered the highest migration speed, albeit in random directions. The results suggest that electric pulses are vital to galvanotaxis and non-DCEF is promising in both basic and clinical researches.